KEARIFAN LOKAL NELAYAN BAGAN SUKU BUGIS DALAM PEMANFAATAN SUMBERDAYA PERIKANAN DI DESA MUARA BADAK ILIR KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA - Wasada Ansar; Elly Purnamasari; Nurul Ovia Oktawati (Jurnal Pembangunan Perikanan dan Agribisnis, 2020)
The purpose of this research is to study the characteristics of fishermen and forms of local wisdom practiced by the fishing community of the Bugis tribe in Muara Badak Ilir Village. The study was conducted for 7 months. The sampling method used in this study was a purposive sampling method with 7 respondents. Data were analyzed using qualitative descriptive methods. The results of the study illustrate that the fishing communities of Muara Badak Ilir Village are predominantly Bugis ethnicity, graduated from elementary school level, are Muslim, range in age from 50 to 70 years, and are generally small scale fishermen. Some local wisdom regarding Utilization of Fisheries Resources can be seen from (1) Abstinence and Belief: Beach Party (mappanre tasi), saying goodbye before catching, abstinence of reprimanding or greeting fishermen who will go to sea, returning home if there is something left to take to sea, not go to sea on Friday and don't go to sea when someone dies (2) Ethics and Rules: There are rules about prohibiting littering at sea, cutting mangrove trees freely (3). Engineering and Technology: take into account the condition of the sea with natural signs, the use of traditional or environmentally friendly fishing gear, the fisherman's departure time (4). Selective in choosing the type of catch, do not take catches such as turtles, diversification of fishery processing. Keywords: Local Wisdom of Bagan Fishermen, Bugis Etnic, Utilization of Fisheries Resources.